2020
DOI: 10.1186/s13014-020-1481-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for geriatric head-and-neck cancer patients: what is the value of standard treatment in the elderly?

Abstract: Background Head-and-neck squamous cell carcinoma (HNSCC) is one of the most common malignancies globally, and the number of elderly patients diagnosed with HNSCC is increasing. However, as elderly HNSCC patients are underrepresented in clinical trials, current clinical decision making for this cohort largely lacks clinical evidence. Methods Elderly patients (≥65 years) with HNSCC undergoing (chemo)radiotherapy from 2010 to 2018 at Freiburg Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 43 publications
5
62
3
Order By: Relevance
“…Additionally, retrospective analyses of treatment-related toxicities especially of chronic adverse reactions are complicated, as follow-up consultations were not performed by all patients especially during end-of-life phases, leading to underrepresentation of treatment-related toxicities. Especially chronic toxicities such as chondronecrosis or soft tissue fibrosis were not routinely assessed in our cohort and may be underrepresented, as other series reported significantly higher rates of these chronic normal tissue reactions after re-irradiation [46][47][48]. Although the median OS of 25 months was relatively satisfying in our study, the median PFS of 9 months underlines the importance of additional treatment modalities in order to improve both locoregional control and distant metastasis-free survival.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, retrospective analyses of treatment-related toxicities especially of chronic adverse reactions are complicated, as follow-up consultations were not performed by all patients especially during end-of-life phases, leading to underrepresentation of treatment-related toxicities. Especially chronic toxicities such as chondronecrosis or soft tissue fibrosis were not routinely assessed in our cohort and may be underrepresented, as other series reported significantly higher rates of these chronic normal tissue reactions after re-irradiation [46][47][48]. Although the median OS of 25 months was relatively satisfying in our study, the median PFS of 9 months underlines the importance of additional treatment modalities in order to improve both locoregional control and distant metastasis-free survival.…”
Section: Discussionmentioning
confidence: 76%
“…The two-year overall survival (OS), progression-free survival (PFS) and local/locoregional control (LRC) of our elderly HNSCC cohort ranged at 56.9%, 44.9% and 75.5%, respectively ( Figure S2 ) [ 18 ]. Baseline anemia, defined as a hemoglobin level below 12 g/dL, resulted in significantly impaired PFS ( p < 0.01, log-rank test) and OS (HR = 1.536, 95% CI 1.058–2.231, p < 0.05), while LRC was not influenced ( p = 0.332) ( Figure 2 A–C, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…One hundred and forty-seven patients (59.8%) received concomitant systemic treatment, mostly with platinum-based regimens. Detailed patient and treatment characteristics were described previously and can be found in Table 1 and Table S1 [18]. Fisher's exact tests were carried out to reveal potential differences between the radiotherapy and chemoradiotherapy group.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…As a patient's chronologic age alone provides insufficient information regarding the optimal treatment decision, geriatric assessments have proven their value in predicting treatment tolerance and compliance [6]. Whereas more and more studies have demonstrated both the feasibility and the effectiveness regarding radiotherapy for elderly patients, radiotherapy for patients aged ≥90 years is poorly studied in the literature [7][8][9][10]. Although there is a limited number of retrospective studies analyzing the treatment outcomes of radiotherapy for nonagenarian patients, evidence regarding radiotherapy for this patient group remains poor due to relatively low patient numbers in most of these studies [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%